2009
DOI: 10.1016/j.chaos.2008.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Spin-transfer torque induced reversal in magnetic domains

Abstract: Using the complex stereographic variable representation for the macrospin, from a study of the nonlinear dynamics underlying the generalized Landau-Lifshitz(LL) equation with Gilbert damping, we show that the spin-transfer torque is effectively equivalent to an applied magnetic field. We study the macrospin switching on a Stoner particle due to spin-transfer torque on application of a spin polarized current. We find that the switching due to spin-transfer torque is a more effective alternative to switching by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…(11) or (14) using variable step size Runge-Kutta method. In figure 1 we have shown the switching dynamics of the magnetization in the free layer [15]. It can be observed that the direction of magnetization gets reversed at the point m = (1, 0, 0).…”
Section: Switchingmentioning
confidence: 98%
See 3 more Smart Citations
“…(11) or (14) using variable step size Runge-Kutta method. In figure 1 we have shown the switching dynamics of the magnetization in the free layer [15]. It can be observed that the direction of magnetization gets reversed at the point m = (1, 0, 0).…”
Section: Switchingmentioning
confidence: 98%
“…This spin-polarized current exerts a torque on the free layer, which is termed as spin transfer torque (STT), and this exerts a rich variety of dynamics in the free layer. The expression for this torque has been given by Slonczewski and the redefined LLG equation with the STT is read as [7,15] …”
Section: Spin Transfer Torque -Llgs Equationmentioning
confidence: 99%
See 2 more Smart Citations
“…The switching time due to the spin-current is roughly 0.2 ns, while that due to the magnetic field is slower, at nearly 0.7 ns, accompanied by a ringing effect. This delay and ringing effect are well understood to be due to the fact that, even with α = 0, a spin-transfer-torque leads to both precession and dissipation whereas a magnetic field alone can only cause a precession of magnetization vector about the applied field [23]. Field induced switching is thus exclusively due to the damping factor, leading to a longer switching time, consequently.…”
Section: A Logic Nor Gatementioning
confidence: 99%